Dramatic imaging changes of a biliary stricture within 8 months in a rare case - Yue, Ping; Bai, Bing; Zhai, Yanan; Lin, Yanyan; Meng, Wenbo; Li, Xun (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Yue P, Bai B, Zhai Y, Lin Y, Meng W, Li X. Dramatic imaging changes of a biliary stricture within 8 months in a rare case. Turk J Gastroenterol 2020; 31(2): 180-3.